EFFICIENT FUZZY LEFT SHIFT-SINUSOIDAL PULSE WIDTH MODULATION CONTROL SCHEME FOR SERIES ACTIVE POWER FILTER BASED ON SEVEN-LEVEL NEUTRAL POINT CLAMPED INVERTER TOPOLOGIES (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper presents the performance of a series active power filter (APF) based on a seven-level neutral point clamped (NPC) inverter using modified instantaneous reactive power control strategies. Today, multilevel inverters are being investigated and used in various industrial applications. Fuzzy control techniques are successfully employed in various applications; they represent a good alternative to classic control systems. To benefit from all these advantages, a novel control scheme for series APF based on a seven-level neutral point clamped (NPC) inverter using level-shifted multicarrier modulation and fuzzy control approach is proposed in this work. The simulation is carried out using MATLAB-Simulink and SimPowerSystem software. The results show the effectiveness and robustness of the proposed control scheme adopted for the series active power filter system in compensating harmonics and all voltage disturbances.
Keywords: Seven-level neutral point clamped inverter; Series active power filter; Power quality improvement; Fuzzy logic control; Left shift-sinusoidal pulse width modulation